Activity-Dependent Neuroplastic Changes in Autonomic Circuitry Modulating Cardiovascular Control: The Essential Role of Baroreceptors and Chemoreceptors Signaling - Rocha-Santos, Carla; Braga, Douglas Costa; Ceroni, Alexandre; Michelini, Lisete C. (Frontiers in Physiology, 2020)
Aerobic exercise training improves the autonomic control of the circulation. Emerging evidence has shown that exercise induces neuroplastic adaptive changes in preautonomic circuitry controlling sympathetic/parasympathetic outflow to heart and vessels. The mechanisms underlying neuronal plasticity are, however, incompletely understood. Knowing that sinoaortic denervation blocks training-induced cardiovascular benefits, we investigate whether baroreceptors’ and chemoreceptors’ signaling are able to drive neuronal plasticity within medullary and supramedullary pathways controlling autonomic outflow. Male Wistar rats submitted to sinoaortic denervation (SAD) or dopamine -hydroxylase-saporin lesion (DBHx) and respective controls (SHAM) were allocated to training (T) or sedentary (S) protocols for 8 weeks. After hemodynamic measurements at rest, rats were deeply anesthetized for brain harvesting. The density of DBH and oxytocin (OT) cell bodies and terminals were analyzed in brainstem and hypothalamic brain areas (double immunofluorescence reactions, optic and confocal microscopy). In SHAM rats training augmented the density of DBH+ neurons in the nucleus of solitary tract, increased the density of ascending NORergic projections and the number of DBH+ boutons contacting preautonomic OT+ neurons into paraventricular hypothalamic preautonomic nuclei, augmented the density of local OTergic neurons and enhanced the density of OT+ terminals targeting brainstem autonomic areas. These plastic changes occurred simultaneously with reduced sympathetic/increased parasympathetic activity, augmented baroreflex sensitivity and reduced resting heart rate. SAD reduced the density of both DBH+ fibers ascending from brainstem to PVN and preautonomic OT+ neurons projecting to the brainstem, abrogated training-induced plastic changes and autonomic adaptive responses without changing the treadmill performance. Minor neuroplastic changes with preserved baroreflex sensitivity were observed in trained rats after partial selective disruption of ascending NORergic projections. Our data indicated that afferent inputs conveyed by arterial baroreceptors and chemoreceptors are the main stimuli to drive both inactivity-induced and activity-dependent neuroplasticity within the autonomic circuitry.